2016
DOI: 10.1051/0004-6361/201628361
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic signatures of magnetospheric accretion in Herbig Ae/Be stars

Abstract: Context. Models of magnetically-driven accretion and outflows reproduce many observational properties of T Tauri stars. This concept is not well established for the more massive Herbig Ae/Be stars. Aims. We intend to examine the magnetospheric accretion in Herbig Ae/Be stars and search for rotational modulation using spectroscopic signatures, in this first paper concentrating on the well-studied Herbig Ae star HD 101412. Methods. We used near-infrared spectroscopic observations of the magnetic Herbig Ae star H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Except for the region around the stellar rest velocity, the entire line is correlated, which indicates that most of this line is formed in a single region of the system. Many authors have suggested that HBe systems, like V590 Mon, are not simple scaled versions of CTTS, and that there is no clear evidence that magnetospheric accretion is ongoing in these systems (Vink et al 2002;Cauley & Johns-Krull 2014Ababakr et al 2015;Fairlamb et al 2015;Schöller et al 2016). The Hα emission line may therefore come mostly from a high density wind without a significant magnetospheric accretion contribution (Boehm & Catala 1995).…”
Section: Correlation Matricesmentioning
confidence: 99%
“…Except for the region around the stellar rest velocity, the entire line is correlated, which indicates that most of this line is formed in a single region of the system. Many authors have suggested that HBe systems, like V590 Mon, are not simple scaled versions of CTTS, and that there is no clear evidence that magnetospheric accretion is ongoing in these systems (Vink et al 2002;Cauley & Johns-Krull 2014Ababakr et al 2015;Fairlamb et al 2015;Schöller et al 2016). The Hα emission line may therefore come mostly from a high density wind without a significant magnetospheric accretion contribution (Boehm & Catala 1995).…”
Section: Correlation Matricesmentioning
confidence: 99%
“…The right of Figure 3 illustrates the phase dependencies of the He I λ10830 line taken from [17,18]. As the MA model predicts, the V r2 parameter is at its maximum when B z reaches its minimal or maximal value.…”
Section: The Magnetic Herbig Ae Star Hd 101412mentioning
confidence: 88%
“…A second outcome of their research was the confirmation that Herbig Ae stars are similar to T Tauri stars in displaying a line polarization effect, while depolarization is more common among Herbig Be stars. Using near-infrared multi-epoch spectroscopic data obtained with the CRIRES and X-shooter spectrographs installed at the VLT, Schöller et al (2016) examined the magnetospheric accretion in the Herbig Ae star HD 101412. Spectroscopic signatures in He I 10830 and Paγ, two near-infrared lines that are formed in a Herbig star's accretion region, were presenting temporal modulation.…”
Section: Future Work On Stellar Properties Of Magnetic Herbig Stars Smentioning
confidence: 99%